EVALUATION OF PROBIOTIC MICROENCAPSULATION IN A PREBIOTIC MIXTURE WITH COFFEE EXTRACT - Zapata, Angela María Ormaza; Arango, Felix Octavio Díaz; Rodríguez-Barona, Sneyder (Coffee Science - ISSN 1984-3909, 2019)
The objective in the present study was to evaluate coffee extract as an encapsulant material, when mixed with prebiotic carbohydrates, in order to obtain a coffee-based, non-dairy probiotic beverage. Six coffee extract formulations were evaluated with maltodextrin and inulin, in various proportions, for the obtaining of microcapsules with the probiotic strain L. casei ATCC 393, by way of spray drying. The best formulations encountered were MD-INU:EXT (50:50) and EXT:Water (50:50), which were spray dried, for increased viability, elevated wettability and solubility, low hygroscopicity, and adequate morphology for this type of powdered product. The formulation was composed of maltodextrin, inulin, and coffee extract, and MD-INU:EXT (50:50) presented the best physicochemical and viability characteristics. The potential of coffee extract was proven as a wall material in microencapsulated, non-dairy, highly acidic, probiotic products. Optimal viability was achieved, in the order of 1x106 CFU/mL, for both selected formulations, which maintained functional potential for up to 11 weeks of storage.